2021
DOI: 10.1016/j.redox.2021.102091
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals lasting changes in the lung cellular landscape into adulthood after neonatal hyperoxic exposure

Abstract: Ventilatory support, such as supplemental oxygen, used to save premature infants impairs the growth of the pulmonary microvasculature and distal alveoli, leading to bronchopulmonary dysplasia (BPD). Although lung cellular composition changes with exposure to hyperoxia in neonatal mice, most human BPD survivors are weaned off oxygen within the first weeks to months of life, yet they may have persistent lung injury and pulmonary dysfunction as adults. We hypothesized that early-life hyperoxia alters the cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…In primary neonatal human alveolar epithelial cells in vitro we showed that HOX cell-autonomously induces expression of the inflamed AT2 and DATP signatures, suggesting a conserved response across species. Scafa et al used a brief exposure to HOX (P1-P3) to study AT1 and AT2 populations using scRNA-seq, and while they identified several AT clusters, they did not comment on the populations we identified 95 . Whether this response is able to reconstitute the AT1 pool, and the key signaling mechanisms mediating it, are topics for future research.…”
Section: Discussionmentioning
confidence: 97%
“…In primary neonatal human alveolar epithelial cells in vitro we showed that HOX cell-autonomously induces expression of the inflamed AT2 and DATP signatures, suggesting a conserved response across species. Scafa et al used a brief exposure to HOX (P1-P3) to study AT1 and AT2 populations using scRNA-seq, and while they identified several AT clusters, they did not comment on the populations we identified 95 . Whether this response is able to reconstitute the AT1 pool, and the key signaling mechanisms mediating it, are topics for future research.…”
Section: Discussionmentioning
confidence: 97%
“…To test this hypothesis, we exposed newborn mice to hyperoxia in the saccular stage (postnatal day 0–3, pnd 0–3) to mimic lung injury in BPD. Some mice were then allowed to recover in room air until adulthood, because short-term neonatal hyperoxic exposure has long-term effects on lung function and causes persistent alveolar simplification in mice 18 , 19 . We assessed the ontogeny of cellular senescence at different stages of postnatal lung development to study whether senescence participates in normal lung alveolarization and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…An miRNAScope HD (RED) Assay (ACDBio, Newark, CA, USA) was performed as previously described with modifications for miRNA [ 35 ]. In brief, lung sections were deparaffinized using xylene followed by incubation with hydrogen peroxide to block endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%